Metal deficiency tuned charge transfer in intermetallic Ni2-xSn (x =0.37-0.65) enhances selective conversion of furfural to furfuryl alcohol towards the theoretical limit - Cherevotan, Arjun; Singh, Ashutosh Kumar; Yadav, Anish; Maligal-Ganesh, Raghu V.; Raj, Jithu; Pulparambil, Anu; Goud, Devender; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2025)
Heterogeneous catalysis facilitated by intermetallic nanoparticles has recently been the subject of increased scrutiny, given the enhanced selectivity and stability they bestow on many chemical reactions compared to their monometallic components. This paper explores a series of Ni-Sn (Ni2-xSn, where x = 0.65, 0.5, 0.37) intermetallic compounds supported on a high-surface-area support, SBA-15, as catalysts for the selective hydrogenation of furfural to furfuryl alcohol. Rietveld refinements of the X-ray diffraction data show catalysts with mixed intermetallic phases that assist in the catalysis. At the same time, X-ray photoelectron spectroscopy (XPS) studies and X-ray absorption studies indicate the role played by charge transfer from Sn to Ni for the catalysis. Selectivity to the desired furfuryl alcohol in all the intermetallic samples was high (>97%), but Ni1.35Sn had a relatively lower conversion than the other intermetallic compounds.